Wycliffism and Hussitism - Ghosh, Kantik; Soukup, Pavel (Brepols, 2021)
John Wyclif (d. 1384), famous Oxford philosopher-theologian and controversialist, was posthumously condemned as a heretic at the Council of Constance in 1415. Wyclif’s influence was pan-European and had a particular impact on Prague, where Jan Hus, from Charles University, was his avowed disciple and the leader of a dissident reformist movement. Hus, condemned to the stake at Constance, gathered around him a prolific circle of disciples who changed the landscape of late medieval religion and literature in Bohemia, just as Wyclif’s own followers had done in England. Both thinkers, and the movements associated with them, played a crucial role in the transformation of later medieval European thought, in particular through a radically enlarged role of textual production in the vernaculars (especially Middle English and Old Czech), as well as in Latin, in the philosophical, theological, and ecclesiological realms. This interdisciplinary volume of essays brings together cutting-edge research from scholars working in these and contiguous fields and asks fundamental questions about the methods that informed Wycliffite and Hussite writings and those by their interlocutors and opponents. Viewing these debates through a methodological lens enables a reassessment of the impact that they had, and the responses they elicited, across a range of European cultures, from England in the west via France and Austria to Bohemia in the east.